Senior sexual and gender minorities' perception of healthcare services: A phenomenological approach. (2nd October 2021) - Benoit, Ilgım Dara; Kordrostami, Elika; Foreman, Jeff
ABSTRACT: The purpose of this research is to explore the sexual and gender minority seniors' experience and perception of healthcare services. A phenomenological focus group study was conducted by interviewing members of a local LGBT seniors' organization in the Northeastern USA. The results of the exploratory research study are threefold. First, the participants were not particularly concerned about the everyday interaction with their healthcare providers, finding their gender and sexuality irrelevant to their daily healthcare visits. Second, they were worried about their financial stability and future on account of covering healthcare costs. This is partly because they have less income and family support compared to the general population. Third, the most important shared concern was whether the long-term healthcare facilities, such as nursing homes, would be culturally competent. The findings of current research also highlight that participants were not aware of any particular facility that is inclusive of all gender and sexual identities. In conclusion, long-term healthcare facilities (e.g. nursing homes, assisted-living facilities) should invest in the inclusiveness training of their employees. Also, healthcare facilities could benefit from emphasizing the inclusiveness of their facility in their communications to this profile. Theoretical and managerial implications, and future research opportunities are also discussed.